What helps adolescents with obesity to enjoy and participate in physical activity? - Constanze Greule; Gorden Sudeck; Katrin Ziser; Rebecca Erschens; Peter Martus; Katrin Elisabeth Giel; Isabelle Mack; Alisa Weiland; Guido Zurstiege; Stephan Zipfel; Stefan Ehehalt; Florian Junne; et al. (German Journal of Exercise and Sport Research, 2026)
Purpose The main purpose was to identify clusters of adolescents with overweight or obesity characterized by the satisfaction of basic psychological needs, exercise-related barriers, and social support by family members and friends. This served the overarching goal of informing hypotheses for tailored research approaches in physical activity promotion considering a stronger focus on physical activity enjoyment. Methods Cross-sectional baseline data from 125 adolescents with overweight or obesity aged 12–17 years participating in the STARKIDS study were analyzed. A hierarchical cluster analysis was carried out, and the resulting number of clusters was optimized using the K‑means method. Subsequently, differences between individual cluster membership regarding physical activity enjoyment and physical activity levels were analyzed to further describe the identified subgroups. Results Four psychosocial clusters were identified as (1) overall supportive, (2) overall hindering, (3) individually supportive, and (4) socially supportive. The clusters differ significantly in terms of physical activity enjoyment ( p η 2 = 0.370) and physical activity behavior ( p η 2 = 0.145), with the highest values of enjoyment in clusters (1) and (3). Conclusion The present results indicate promising opportunities for future research on promoting physical activity enjoyment considering adolescents’ individual and social resources.

Identifying and understanding mechanisms in an inhibitory control training in patients with binge-eating-disorder – an exploratory analysis - Sebastian M. Max; Katrin E. Giel; Christian Plewnia; Veronika Lossa; Stephan Zipfel; Kathrin Schag (Appetite, 2025)

Food-related reward sensitivity across the spectrum of body weight and impulsive eating: Pilot findings from a multi-method approach - Elisabeth J. Leehr; Kathrin Schag; Jule Vogel; Thomas Dresler; Stephan Zipfel; Andreas J. Fallgatter; Martin Hautzinger; Udo Dannlowski; Ann-Christine Ehlis; Katrin E. Giel (Appetite, 2023)

The effectiveness of health-oriented leadership interventions for the improvement of mental health of employees in the health care sector: a systematic review - Felicitas Stuber; Tanja Seifried-Dübon; Monika A. Rieger; Harald Gündel; Sascha Ruhle; Stephan Zipfel; Florian Junne (International Archives of Occupational and Environmental Health, 2021)
Purpose An increasing prevalence of work-related stress and employees’ mental health impairments in the health care sector calls for preventive actions. A significant factor in the workplace that is thought to influence employees’ mental health is leadership behavior. Hence, effective leadership interventions to foster employees’ (leaders’ and staff members’) mental health might be an important measure to address this pressing issue. Methods We conducted a systematic review according to the PRISMA statement (Liberati et al. 2009) and systematically searched the following databases: PubMed (PMC), Web of Science, PsycINFO (EBSCOhost), EconLit (EBSCOhost), and Business Source Premier (EBSCOhost). In addition, we performed a hand search of the reference lists of relevant articles. We included studies investigating leadership interventions in the health care sector that aimed to maintain/foster employees’ mental health. Results The systematic search produced 11,221 initial search hits in relevant databases. After the screening process and additional literature search, seven studies were deemed eligible according to the inclusion criteria. All studies showed at least a moderate global validity and four of the included studies showed statistically significant improvements of mental health as a result of the leadership interventions. Conclusions Based on the findings, leadership interventions with reflective and interactive parts in group settings at several seminar days seem to be the most promising strategy to address mental health in health care employees. As the available evidence is limited, efforts to design and scientifically evaluate such interventions should be extended.

Common mental disorders through the eyes of German employees: attributed relevance of work-related causes and prevention measures assessed by a standardised survey - Stephanie Burgess; Florian Junne; Eva Rothermund; Stephan Zipfel; Harald Gündel; Monika A. Rieger; Martina Michaelis (International Archives of Occupational and Environmental Health, 2019)